Paradigm Shift in the Concept of Democracy in Decision Making within Individual Companies - Ali Abdullah; Diani Kesuma; Maria Regina Ivana (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
To enhance economic growth in Indonesia, active community participation through the establishment of companies is crucial. Various types of companies, both non-legal entities and legal entities, exist to meet business needs, including Micro, Small, and Medium Enterprises (MSMEs). With the introduction of the Individual Company concept in Law No. 11 of 2020 on Job Creation, significant changes have emerged in the structure and decision-making mechanisms. The Individual Company allows individuals to establish a business with just one shareholder, eliminating the minimum capital requirement and the need for multiple founders. This shift impacts the democratic principles of decision-making, where strategic decisions are entirely in the hands of one individual, potentially reducing accountability and transparency. This research employs a normative research method. The findings indicate that the Job Creation Law introduces individual companies in Indonesia, allowing individuals to establish companies without partners and removing the minimum capital requirement. This supports Micro and Small Enterprises (MSEs) and emphasizes legal equality in shareholder decisions, despite implementation challenges related to the role of the General Meeting of Shareholders (GMS). The elimination of the GMS and Board of Commissioners in Individual Companies grants absolute power to the single shareholder, increasing the risk of abuse of power. While decision-making becomes more efficient, the lack of control may lead to legal issues and ineffective governance.